PENERAPAN MODEL PEMBELAJARAN TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SDN 2 PELEMKEREP PADA MUATAN PPKN - Alfina Damayanti; Erik Aditia Ismaya; Wawan Shokib Rondli (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of carrying out this research was to improve student learning outcomes by applying the Talking stick learning model to the PPKn learning content theme 9. This research was conducted in May 2023. The research method used was classroom action research which lasted for 2 cycles where each cycle consisted of four stages namely planning, implementation, observation, and reflection. The subjects in this study were 17 students in class V, with 9 male students and 8 female students. In conducting this research using four techniques in data collection, namely interviews, observation, tests, and documentation. Learning outcomes in the domain of knowledge from cycle I which obtained a classical mastery percentage of 64.2% then in cycle II increased to 82.4%. The learning outcomes in the domain of skills have increased from cycle I which obtained an average of 66.78% then increased in cycle II which obtained an average of 76.59%. The learning outcomes in the attitude domain experienced an increase from cycle I which obtained an average of 68.99% then in cycle II it increased to 76.34%. Based on the results obtained, it was concluded that the application of the Talking Stick learning model could improve student learning outcomes in PPKn content.